Costs of Sleep Endoscopy With Same‐Day Versus Staged Surgery for Pediatric Obstructive Sleep Apnea - Nicholas R. Lenze; Michael M. Allevato; William J. Benjamin; Emmanuel Servin; Erin M. Kirkham; David A. Zopf; Joseph G. Sinnwell (OTO Open)
Abstract Objective To compare the costs of staged versus same‐day surgery after drug‐induced sleep endoscopy (DISE) for pediatric obstructive sleep apnea (OSA). Study Design Retrospective cohort study. Setting Single tertiary‐care center in the United States from 2017 to 2023. Methods Patients were grouped into two surgical pathways: (1) DISE with same‐day OSA surgery and (2) DISE with staged OSA surgery. Nonparametric tests and log‐normal models were used to compare insurance payments, out‐of‐pocket costs, and hospital costs between pathways and to evaluate predictors of hospital costs. Results A total of 57 pediatric OSA patients with a mean (standard deviation [SD]) age of 10.8 (4.0) years were included. The mean insurance payments, out‐of‐pocket costs, and hospital costs were $12,158 (SD 10,412), $340 (SD 1168), and $11,965 (SD 9615), respectively. Patients who underwent DISE with staged OSA surgery had significantly higher hospital costs than those who underwent DISE with same‐day OSA surgery (mean difference $8995, 95% CI 3528‐14462; P < .001), and this effect persisted in an adjusted log‐normal model (coefficient 0.82, 95% CI 0.34‐1.30; P = .001). There were no significant differences in insurance payments or out‐of‐pocket costs by surgical pathway. Conclusion DISE with staged OSA surgery conferred higher hospital costs than DISE with same‐day OSA surgery but did not increase financial burden on patients or payers. This finding has important implications for resource utilization for a common pediatric condition.